Factors Influencing Mortality after Bioprosthetic Valve Replacement; A Midterm Outcome - Hassan Javadzadegan; Amir Javadzadegan; Jafar Mehdizadeh Baghbani (Journal of Cardiovascular and Thoracic Research, 2013)
Introduction: Although valve repair is applied routinely nowadays, particularly for mitral regurgitation (MR) or tricuspid regurgitation (TR), valve replacement using prosthetic valves is also common especially in adults. Unfortunately the valve with ideal hemodynamic performance and long-term durability without increasing the risk of bleeding due to long-term anticoagulant therapy has not been introduced. Therefore, patients and physicians must choose either bioprosthetic or mechanical valves. Currently, there is an increasing clinical trend of using bioprosthetic valves instead of mechanical valves even in young patients apparently because of their advantages. Methods: Seventy patients undergone valvular replacement using bioprosthetic valves were evaluated by ECG and Echocardiography to assess the rhythm and ejection fracture. Mean follow-up time was 33 months (min 9, max 92). Results: Mortality rate was 25.9% (n=18) within 8 years of follow-up. Statistical analysis showed a significant relation between atrial fibrillation rhythm and mortality (P=0.02). Morbidities occurred in 30 patients (42.8%). Significant statistical relation was found between the morbidities and age over 65 years old (P=0.005). In follow-up period, 4 cases (5.7%) underwent re-operation due to global valve dysfunction. Conclusion: Our study shows that using biprosthetic valve could reduce the risk of morbidity occurrence in patient who needs valve replacement. However, if medical treatments fail, patients should be referred for surgery. This would reduce the risk of mortality because of lower incident of complications such as atrial fibrillation and morbidities due to younger patients’ population.